(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Guided Bone Regeneration is a surgical treatment that involves the use of barrier membranes, particulate bone transplants, and/or bone substitutes. Sheep's weighted 20-30 kg were intubated and underwented general sedation with 0.03 mg / kg IM xylazine. The 8ml of blood was taken from external jugular vein of the sheep and immediately transferred in to citrated tube and transferred to centrifuge to prepare the PRP gel. The produced PRP was mixed with chitosan in 95:5 ratio. With a round bur and abundant irrigation, a 4-5 mm round osteotomy was formed in the pad of the maxilla with two in the right and two in the left side. Four equal defects were grafted with experimental material composed of mixed PRP and chitosan (95:5 ratio). After four weeks, the result show new bone formation around the defect side which was associated with interrupted fibrous connective tissue capsule for some of the samples with focal active osteoblasts. In ten weeks, the results show thick bones were newly formed at the defect side with remnants of chitosan observed at the site of bone. In conclusion: the present study revealed the combination of PRP and Chitosan accelerates the healing and regeneration of bones.